Analisis Beban Kerja Mental Pada Mekanik Menggunakan Metode SWAT dan Metode QNBM - Yolanda Lapai; Idham Halid Lahay; Fentje Abdul Rauf (Jurnal Teknik, 2020)
Mental workload is the difference between the demands of a task workload with the maximum capacity of a person's mental capability in a motivated state. The purpose of this study was to determine the level of the mental burden of mechanics using the SWAT and QNBM methods. The results of the Subjective Workload Assessment Technique method for heavy service workload showed that the mechanics were 56.6% burdened. Mental workload dimensions for mechanics 1 and 3 are effort load, for mechanic 2 is time load. The category for light service is 11.11%, unburdened in the time load dimension for all mechanics. Nordic Body Map Questionnaire Method was 67%, with illness category included.